STABILITAS MIKROKAPSUL OLEORESIN PALA (Myristica fragrans Houtt) TERHADAP SUHU DAN KELEMBABAN RUANG PENYIMPANAN - , MUHAMMAD ASSAGAF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nutmeg (Myristica fragrans Houtt) Oleoresin is a form of ethanol extract of nutmeg that has characters close to nutmeg flavor. Oleoresin extraction conditions would the amount and quality of oleoresin produced. When oleoresin is exposed by oxygen, light, temperature and humidity, it could be easily impaired. This problem is could be solved by microencapsulation technology. The advantages of microencapsulation are to protect the flavor and aroma during processing and storage of food products as well as to control the release of the active components. In general, the objective of this study it to obtain information to what extent the nutmeg oleoresin microcapsules stability could sustain against the temperature and humidity. In terms of specific objectives, this study is to: (1) gain the optimum conditions of temperature and time on nutmeg oleoresin extraction, (2). determine the mixture ratio of whey protein concentrate (WPC) : maltodextrin (MD) as encapsulant for nutmeg oleoresin microencapsulation, (3). obtain information on nutmeg oleoresin microcapsules stability against temperature, and (4). collect information on nutmeg oleoresin microcapsules stability against moisture. This research was conducted as a follow up study of the previous research in term of the optimization of extraction conditions for gaining oleoresin by using Response Surface Methodology (RSM) with two factors Central Composite Design (CCD) design, namely temperature (45, 50 and 55 o C) and time (240, 270 and 300 minutes) and identification the component compound of nutmeg oleoresin using GC-MS. In addition, there should be any determination of encapsulant ratio of a mixture of ratio WPC : MD which is able to protect oleoresin to produce microcapsules which have a low surface oil. The examined encapsulant is the mixture of WPC (0-24%) and MD (100-76%), which has been combined in 7 fusions. The suspension of a mixture of WPC and MD in water is set at the total solid on 1:9 is dried using a spray drier at the temperature of inlet 160 o C and feed flow rate at 300ml/hour. The resulting microcapsules are used to analyze the surface oil, total volatile, non-volatile, water content, water activity and the morphology of its microcapsules. Nutmeg oleoresin microcapsules is observed by storing it at 30, 40, 50, 60 and 70 o C. The kinetics oleoresin of degradation in terms of its total volatile oleoresin and its shelf life prediction are evaluated using the Arrhenius equation model and nutmeg oleoresin microcapsules are stored at the various humidity level of 34, 68, 74, 88 and 97%. Shelf life prediction and ISL curve are evaluated using equilibrium moisture content during storage was evaluated using the BET and GAB equations models Results showed that the optimum conditions for nutmeg oleoresin extraction were at 51.98Â°C and 273.8 minutes, which produced the yields of 14.88%. The resulting nutmeg oleoresin has 47 components with three chemical compounds that determine flavor of nutmeg oleoresin so-called myristicin (10.90%), elemicin (4.66%), and safrole (0.64%). The best results of nutmeg oleoresin microcapsules are derived from a mixture of 12% WPC encapsulant and MD 88%. These microcapsules have low surface oil (0.16%) and higher total volatile (26.7%) with average water content of 3.4% (db), water activity between 0.29 to 0.41, efficiency microencapsulation of 66,8% and particle size between 1.39 to 56.6 Î¼m. Microcapsules storage at temperature of 30 to 70Â°C resulted in microcapsule with water content 5.75-3.28%, degrees of whiteness at 73.22- 64.21, ether extract at 96.63-80.97%, non-volatile compounds at 72.69-80.97%, total volatiles at 23.94-8.39%, and surface oil from 0.136-0.67%. Shelf life with total volatile as parameters has lasted for 35, 32, 28, 26 and 23 weeks. Microcapsules storage is set at humidity level of 34, 68, 74, 88, and 97%, at moisture content from 3.49-38.3%, at degree of whiteness of 71.98-39.66, at ether extract of 73.42-78.95%, at non-volatile compounds of 81.47-85.5%, and at total volatiles from 21.02-8.30%. Shelf life of packed microcapsules with 0.08 mm thick polypropylene plastic using the BET model resulted 8.3 weeks and 9 weeks of GAB models. In general, it can be concluded that stability of oleoresin microcapsules are affected by variable of temperature and storage time. Higher temperature and longer storage time will cause the decrease in the degree of whiteness, total volatile, ether extract and aromatic fractions, especially myristicin, methyl eugenol, and elemicin of nutmeg oleoresin microcapsules. Shelf life of nutmeg oleoresin microcapsules based on total volatiles becomes shorter when storage temperature is increasingly higher, ranging from 35 weeks to 23 weeks. While the stability of the microcapsules oleoresin stored at RH 34 to 97% decrease in physical and chemical stability, especially at RH above 68%. The decrease in stability can be seen from the decline in degree of whiteness by 54% of the microcapsules showed a brownish yellow color, rising moisture content levels, declining total volatile and being cacking which can be seen on is microcapsule morphology using SEM. The increase of equilibrium water content of microcapsules nutmeg oleoresin which is stored at RH 34 up to 97% based on moisture sorption isotherm curves (ISL) indicates the type of dry food groups as described by the BET and GAB equations as type of sigmoid curve. Shelf life of microcapsules on those two equations which if stored using plastic packaging of polypropylene is longer than using polyethylene plastic.